2009
DOI: 10.1108/09684880910992340
|View full text |Cite
|
Sign up to set email alerts
|

Teaching effectiveness, impression management, and dysfunctional behavior

Abstract: PurposeStudent evaluation of teaching (SET) questionnaires are used in many countries, although much current research questions the validity of these surveys. US research indicates that more than 90 percent of academic accounting departments use this performance measurement. This paper aims to focus on the validity of SET data.Design/methodology/approachA mail survey was sent to a random sample of 1,000 accounting professors employed at four‐year universities and colleges in the USA. A total of 447 responses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Need to assess other classroom dynamics to supplement SET scores Crumbley & Reichelt (2009) Instructors (i.e., teachers and/or faculty members) engage in impression management when SET data are used for control purposes. Such dysfunctional behaviour identified in accounting instructors include easy grading, coursework deflation and other defensive strategies with negative social implications (see p. 377).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Need to assess other classroom dynamics to supplement SET scores Crumbley & Reichelt (2009) Instructors (i.e., teachers and/or faculty members) engage in impression management when SET data are used for control purposes. Such dysfunctional behaviour identified in accounting instructors include easy grading, coursework deflation and other defensive strategies with negative social implications (see p. 377).…”
Section: Discussionmentioning
confidence: 99%
“…This new use has moved from the back burner to the forefront of the evaluation mechanism. Consequently rather than use SET to identify student learning and achievement, SET seems to have become a basis for faculty promotions decisions and merit pay awards (see Crumbley & Reichelt, 2009).…”
mentioning
confidence: 98%
“…While proponents argue that SET lead to increased teaching and learning quality, critics suspect negative impacts on staff motivation and compliant behavior as a self-protective measure (Crumbley & Reichelt, 2009;Simpson & Siguaw, 2000), misinterpretation, abuse, even cruelty by students (Chan, Luk, & Zeng, 2014;Clayson, 2005;Hajdin & Pažur, 2012;Lindahl & Unger, 2010) or simply a lack of validity in indicating student achievements (Galbraith, Merrill, & Kline, 2012). For the aspect of quality knowledge mediation the aspect of self-protection by the teacher (researcher) and compliant behavior is crucial: if the SET are used as criteria for tenure or promotions, teachers (researchers) behave rationally by decreasing the course level to the lowest common denominator in order to receive favorable SET.…”
Section: Communicationmentioning
confidence: 99%
“…While originally developed to provide instructors feedback in order to improve their teaching (Surgenor, 2013), universities subsequently began to use SET as a tool for faculty performance, promotion, and tenure evaluation. A study of US accounting instructors reported that universities used SET for evaluation of teaching effectiveness (95%), tenure (87%), promotion (85%), and merit pay (70%) (Crumbley & Reichelt, 2009). More recently, universities have begun to use SET as an instrument for institutional quality-assurance and accountability, a practice that is gaining popularity in places like Australia (Smithson et al, 2015) and Europe, particularly Ireland (Surgenor, 2013).…”
Section: Introductionmentioning
confidence: 99%